Impact of repeated annual community directed treatment with ivermectin on loiasis parasitological indicators in Cameroon: Implications for onchocerciasis and lymphatic filariasis elimination in areas co-endemic with Loa loa in Africa - Wanji, Samuel; Chounna Ndongmo, Winston Patrick; Fombad, Fanny Fri; Kengne-Ouafo, Jonas Arnaud; Njouendou, Abdel Jelil; Longang Tchounkeu, Yolande Flore; Koudou, Benjamin; Bockarie, Moses; Fobi, Grace; Roungou, Jean Baptiste; Enyong, Peter A. (PLOS Neglected Tropical Diseases, 2018)
Author summary Loa loa (the parasite causing loiasis), also known as African eye worm, is endemic in forest areas of west and central Africa. In several of the endemic areas, it co-exists with onchocerciasis and lymphatic filariasis (LF). Because of the benefit individuals suffering from onchocerciasis could have by taking ivermectin where the disease is severe, despite the risk of developing serious side-effects due to being co-infected with L. loa, mass drug administration (MDA) of ivermectin for the control of onchocerciasis has been ongoing in areas where the two diseases overlap. Ivermectin is also effective against loiasis. It is, therefore, hypothesized that several years of ivermectin MDA against onchocerciasis in those areas may have impacted on parasitological indicators for loiasis. In particular, we assess the impact of annual community directed treatment with ivermectin (CDTI) on loiasis with specific reference to the relationship between adherence to treatment and the risk of developing severe (nervous system) complications following ivermectin treatment. We also discuss the feasibility of eliminating onchocerciasis and/or LF in areas endemic for L. loa with ivermectin as the sole intervention tool.